Noncanonical Ion Channel Behaviour in Pain - Ciotu, Cosmin I.; Tsantoulas, Christoforos; Meents, Jannis; Lampert, Angelika; McMahon, Stephen B.; Ludwig, Andreas; Fischer, Michael J.M. (International Journal of Molecular Sciences, 2019)
Ion channels contribute fundamental properties to cell membranes. Although highly diverse in conductivity, structure, location, and function, many of them can be regulated by common mechanisms, such as voltage or (de-)phosphorylation. Primarily considering ion channels involved in the nociceptive system, this review covers more novel and less known features. Accordingly, we outline noncanonical operation of voltage-gated sodium, potassium, transient receptor potential (TRP), and hyperpolarization-activated cyclic nucleotide (HCN)-gated channels. Noncanonical features discussed include properties as a memory for prior voltage and chemical exposure, alternative ion conduction pathways, cluster formation, and silent subunits. Complementary to this main focus, the intention is also to transfer knowledge between fields, which become inevitably more separate due to their size.
CRIS-Team Scopus Importer:2019-10-01
Keywords: drug development; HCN channel; pharmacology; potassium channel; sodium channel; TRP channel